Epiphytic bryophytes and lichens in Quercus rotundifolia Lam. woodlands of Portugal and their value as ecological indicators - Garcia, C.; Carvalho, P.; Sergio, C.; Sim-Sim, M.; Diogo, A. (Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality, 2005)
The epiphytic bryophyte and lichen vegetation in Quercus rotundifolia woodlands in Portugal and its dependence on a number of environmental variables were investigated in six sites of Portugal. 36 bryophyte (32 mosses, 4 liverworts) and 105 lichens were found. Multivariate analysis was used to examine the epiphytic bryophyte and lichen composition of these woodlands. TWINSPAN and Canonical Correspondence Analysis (CCA) recognized four major groups of bryophytes and lichens species, one related to pastoral woodlands, another to altitudinal woodlands, a third one to the woodlands under Atlantic influence and a fourth with generalist species. Differences in bryophyte and lichen species composition and cover in the studied areas were attributed mainly to distinct humidity, precipitation, evapotranspiration and insolation levels. The bryophytes Leucodon sciuroides, Frullania dilatata, and the lichen Evernia prunastri presented the highest cover values. A very rare bryophyte species Zygodon forsteri, included in the European Red Data Book, was found. Obtained results are a good basis to improve methods based on bryophytes and lichens as bio-indicators of forest biodiversity.
The following values have no corresponding Zotero field: periodical: Monitoring and Indicators of Forest Biodiversity in Europe - From Ideas to Operationality issue: 51 pub-location: TORIKATU 34, FIN-80100 JOENSUU, FINLAND
Keywords: bryophytes; Ecological indicators; lichens; Portugal; TWINSPAN; woodlands